Quantum Google algorithm - Markus Muller (The European Physical Journal Plus, 2014)
We review the main findings on the ranking capabilities of the recently proposed QuantumPageRank algorithm (G.D. Paparo et al., Sci. Rep. 2, 444 (2012) and G.D. Paparo et al., Sci. Rep. 3, 2773(2013)) applied to large complex networks. The algorithm has been shown to identify unambiguously theunderlying topology of the network and to be capable of clearly highlighting the structure of secondary hubsof networks. Furthermore, it can resolve the degeneracy in importance of the low-lying part of the list ofrankings. Examples of applications include real-world instances from the WWW, which typically display ascale-free network structure and models of hierarchical networks. The quantum algorithm has been shownto display an increased stability with respect to a variation of the damping parameter, present in theGoogle algorithm, and a more clearly pronounced power-law behaviour in the distribution of importanceamong the nodes, as compared to the classical algorithm.